Physical Properties of Porcelain Ceramic with Influence of Milled Alkali Resistant (AR) Fibreglass for Sewer Pipes Application / Muhammad Ikhmal Hanapi...[et al.] - Hanapi, Muhammad Ikhmal; Ahmad, Sufizar; Taib, Hariati; Tan, Chee Chen (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The aim of the present work is to explore the use of commercial porcelain ceramic with influence of milled Alkali Resistant (AR) fiberglass for sewer pipes application. In this study, AR fiberglass was milled into an average particle size of 90μm and mixed with porcelain in different weight percentages of 3 wt%, 6 wt%, 9 wt%, and 12 wt%. The sample was prepared by using powder compaction and fired for 2 hours at 900°C, 1000°C, 1100°C and 1200°C. The result of apparent porosity and bulk density were recorded for each sample. Scanning Electron Microscope (SEM) were used to observe the microstructural morphology for some samples. Based on the result, the best sintering temperature was at 1200°C. In which the optimum apparent porosity obtained was 0.30% with addition of 9wt% AR glass. Meanwhile, the best value for density gained was 2.45g/cm3 at 3wt% of AR glass. Reduction of porosity with formation of glassy phase due to the addition of AR glass and elevation of sintering temperature were evident from the microstructural image.